TERT Promoter Mutation C228T Increases Risk for Tumor Recurrence and Death in Head and Neck Cancer Patients - Arantes, Lidia Maria Rebolho Batista; Cruvinel-Carloni, Adriana; de Carvalho, Ana Carolina; Sorroche, Bruna Pereira; Carvalho, André Lopes; Scapulatempo-Neto, Cristovam; Reis, Rui Manuel (Frontiers in Oncology, 2020)
Background: Head and neck squamous cell carcinoma (HNSCC) is usually associated to tobacco and alcohol consumption. Increased telomerase activity has been consistently detected in 80–90% of malignant tumors, including HNSCC. Mutations within the promoter region of telomerase reverse transcriptase (TERT) that confer enhanced TERT promoter activity have been reported in two major hotspots, designated C228T and C250T. Objectives: To evaluate TERT promoter mutations C228T and C250T in HNSCC patients from Brazil and correlate with patients’ outcome. Material and methods: Formalin-fixed paraffin-embedded tissues were obtained from 88 HNSCC patients and analyzed for TERT promoter mutations C228T and C250T by pyrosequencing. Results: The overall prevalence of hotspot TERT mutations in HNSCC samples was of 27,3%, with 6.8% at locus C228T and 20.5% at C250T. The majority (92%) of mutated cases were located in oral cavity, mainly at the tongue. We observed that 94.4% of the patients harboring TERT promoter mutation C250T were alcohol consumers (p=0.032) and 66.7% of the patients harboring TERT promoter mutation C228T were not alcohol consumers (p=0.035). The presence of C228T mutation impacted patient outcome, with a significant decrease in disease-free survival (20.0% vs. 63.0%, p=0.017) and in overall survival (16.7% vs. 45.1%, p=0.017). Conclusion: This is the first report of a TERT promoter mutations in HNSCC patients from South America. The high prevalence of TERT mutation, as well as its association with poor disease-free survival and overall survival, particular at C228T locus might serve as a prognostic biomarker in HNSCC to help clinicians in the management of treatment.